2014
DOI: 10.1016/j.jhep.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The intrahepatic signalling niche of hedgehog is defined by primary cilia positive cells during chronic liver injury

Abstract: In chronic liver injury, Pc(+) progenitors receive Hh ligand signals and process it through Pc/SMO-dependent activation of GLI-mediated transcriptional response. Pc/SMO-independent GLI activation likely occurs in Pc(-)/GLI2(+) cells. Increased fibrosis in Hh gain-of-function mice likely occurs by primary progenitor expansion/proliferation and secondary fibrotic myofibroblast expansion, in close contact with progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 31 publications
4
72
2
Order By: Relevance
“…The Hedgehog pathway is a series of ligands and receptors that have been implicated in a host of homeostatic and pathogenic liver processes including regeneration, fibrogenesis, inflammation, vascular remodeling, and cancer [162]. More recently, Hedgehog has been proposed as an important intermediate regulatory node, which facilitates paracrine crosstalk between damaged hepatocytes and hepatic progenitor cells that expand and contribute to fibrogenesis and myofibroblast activation [163]. The PIVENS trial, which randomized NASH patients to placebo, pioglitazone, or vitamin E, suggested histological response was strongly correlated with loss of the important Hedgehog ligand, Sonic hedgehog [164].…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 99%
“…The Hedgehog pathway is a series of ligands and receptors that have been implicated in a host of homeostatic and pathogenic liver processes including regeneration, fibrogenesis, inflammation, vascular remodeling, and cancer [162]. More recently, Hedgehog has been proposed as an important intermediate regulatory node, which facilitates paracrine crosstalk between damaged hepatocytes and hepatic progenitor cells that expand and contribute to fibrogenesis and myofibroblast activation [163]. The PIVENS trial, which randomized NASH patients to placebo, pioglitazone, or vitamin E, suggested histological response was strongly correlated with loss of the important Hedgehog ligand, Sonic hedgehog [164].…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 99%
“…Irrespective of the injury stimulus, ductular reactions, activated biliary epithelial cells and LPCs are generally closely associated with inflammatory cell populations and fibrosis-driving, activated hepatic stellate cells, forming a very dynamic injury and regeneration niche (Figure 1). Although significant differences in injury and repair dynamics can be observed in different forms of CLD (8), epithelial, inflammatory and fibrogenic cells principally orchestrate liver regeneration versus disease progression through chemokine and cytokine crosstalk in all clinical settings (6,(9)(10)(11)(12)(13). Figure 1.…”
Section: Chronic Liver Disease and The Ductular Reactionmentioning
confidence: 99%
“…Since most of these cell types are not only Hh responding but also secreting cells, depending on those activated states, the concept of intrahepatic signalling niches of Hedgehog suggested by Anna Mae Diehl's group [cf. [5]] and Grzelak and colleagues [1] acquires more attention. Thus, even the normal sinusoid (or possibly the space of Dissé) must be considered as a Hh signalling niche of high complexity, forcing us in the future to focus on the microanatomical environments of cells, local sources and concentrations or gradients of morphogens, and on the different sensitivities of Hh-responsive cells to understand their physiological impact.…”
mentioning
confidence: 99%
“…They demonstrate that the majority, if not all hepatocytes in normal and TAA-treated livers, do not express a primary cilium, whereas primary cilia-positive cell populations, identified as liver progenitor cells (LPCs), occur in injured liver. shown here refer to those occurring after exposure to thioacetamide [1]. Because this cell population as well as HSC and Kupffer cells vary considerably depending on the type and severity of the disease, the spectrum of their Hedgehog signalling may vary as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation